2007
DOI: 10.2337/dc06-1903
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone and Rosiglitazone Have Different Effects on Serum Lipoprotein Particle Concentrations and Sizes in Patients With Type 2 Diabetes and Dyslipidemia

Abstract: OBJECTIVE -Associated with insulin resistance in type 2 diabetes are increased serum triglycerides, decreased HDL cholesterol, and a predominance of large VLDL, small LDL, and small HDL particles. The comparative effects of thiazolidinedione insulin sensitizers on serum lipoprotein particle concentrations and sizes in type 2 diabetes are not known. We studied the effects of pioglitazone (PIO) and rosiglitazone (ROSI) treatments on serum lipoprotein particle concentrations and sizes in type 2 diabetic patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
125
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(145 citation statements)
references
References 39 publications
(28 reference statements)
12
125
1
7
Order By: Relevance
“…The finding that rosiglitazone increases HDL cholesterol is in accordance with previous clinical trials evaluating the effect of rosiglitazone on lipid profile in patients with type 2 diabetes, in which HDL cholesterol levels increased approximately 10 percent [29-31]. These studies also found an adverse effect on low-density lipoprotein (LDL) cholesterol levels after rosiglitazone therapy.…”
Section: Discussionsupporting
confidence: 89%
“…The finding that rosiglitazone increases HDL cholesterol is in accordance with previous clinical trials evaluating the effect of rosiglitazone on lipid profile in patients with type 2 diabetes, in which HDL cholesterol levels increased approximately 10 percent [29-31]. These studies also found an adverse effect on low-density lipoprotein (LDL) cholesterol levels after rosiglitazone therapy.…”
Section: Discussionsupporting
confidence: 89%
“…However, serum levels of conventional lipids and/or lipoproteins remained unchanged. This finding essentially agrees with the report of Deeg et al [21] who used proton nuclear magnetic resonance analysis to show pioglitazone treatment, but not rogiglitazone, caused a significant decrease in both large VLDL and small LDL. In addition, we demonstrated that the changes in large VLDL levels associated with pioglitazone therapy correlated positively with changes in HbA1c, HOMA-IR, very small LDL and emLDL, and correlated negatively with change in adiponectin.…”
Section: Discussionsupporting
confidence: 82%
“…During 24 weeks of treatment, total LDL particle concentration was reduced in the pioglitazone group, but increased in the rosiglitazone group. Both treatments were able to increase LDL particle size, but with pioglitazone having a greater effect [96]. We could confirm these findings in an own study [97].…”
Section: Antihyperglycemic Treatments With Effects On Ldl Particle DIsupporting
confidence: 81%